Psychological analysis of a teacher’s activity in class - TOURCHIN, Anatoly (Journal of Education, Technology and Computer Science, 2013)
In the article written by A.S. Tourchin Psychological analysis of a teacher’sactivity in class a diagram of the teacher’s mastery appraisal evaluated using thenotions of the activity theory by A.N. Leontiev and the theory of an educationalactivity by D. Elkonin and V. Davydov is given.